Innovative Technique Combining Laser Irradiation Effect and Electronic Nose for Determination of Olive Oil Organoleptic Characteristics - Pierpauli, K.; Rinaldi, C.; Azcarate, M. L.; Lamagna, A. (IntechOpen, 2012)
None